1962
DOI: 10.1161/01.res.10.4.658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ventricular Rate on the Cardiac Output in the Dog with Chronic Heart Block

Abstract: The effect of heart rate on cardiac output and associated rate induced hemodynamic changes in dogs with chronic heart block is presented and discussed. At heart rates below 60/min., the stroke volume was maximum and relatively constant, and the cardiac output was largely rate-dependent. These relationships did not exist at ventricular rates above 60/min. Cinefluorographic evidence of decreased diastolic ventricular filling with increasing ventricular rates is presented. At very slow and very fast ventricular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1963
1963
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Miller et al (11) showed by a radiologic technique that end-diastolic size fell when the ventricular rates of chronic heart block dogs was raised. Since the stroke volume response in this preparation is different from that with atrial pacing, the enddiastolic volume response may also differ in the two situations.…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al (11) showed by a radiologic technique that end-diastolic size fell when the ventricular rates of chronic heart block dogs was raised. Since the stroke volume response in this preparation is different from that with atrial pacing, the enddiastolic volume response may also differ in the two situations.…”
Section: Discussionmentioning
confidence: 99%
“…A linear decline in stroke volume as a function of an increase in heart rate has previously been observed [2,7,8]. However, a quantitative evaluation of the changes in left ventricular end-diastolic and end-systolic dimensions during an increase in heart rate has not been reported pre viously.…”
Section: Discussionmentioning
confidence: 94%
“…The decrease in enddiastolic diameter was -2.13 mm/100 beats/min while the end-systolic diameter de clined at a rate of -0.93 mm/100 beats/min. It is concluded that loss of //-adrenergic tone limits stroke volume at high heart rates due to a diminished ability of the myocardium to shorten, as indicated by elevation in the left ventricular end-systolic diameter.Several studies have verified that an increase in heart rate results in a reciprocal decrease in stroke volume in anesthetized or resting, conscious dogs [3,7,8], The changes in stroke volume can be modulated by altera tions in sympathetic nervous system tone [2] or by changes in preload, such as occur with acute volume loading [1], However, there is a paucity of knowledge concerning the changes in left ventricular dimensions which determine the stroke volume response to an increase in heart rate. The purpose of this study is to examine the relation ship between changes in end-diastolic and end-systolic left ventricular dia-…”
mentioning
confidence: 99%
“…An example of an investigation illustrating this type of response is that of Miller et al 3 . These authors stimulated the ventricles of anaesthetised and unanaesthetised dogs with heart block at different frequencies and showed that an increase in the ventricular rate from 60 up to 90 beats/minute resulted in a small increase in cardiac output.…”
Section: E F F E C T O F H E a R T R A T E O N C A R D I A C O U T P U Tmentioning
confidence: 99%